Feed Technology of Fibrous Sugarcane Residues for Ruminants - ., Kuswandi (Indonesian Animal Sciences Society, 2007)
Abundant sugarcane residue during shortage of roughage in dry season gives an opportunity to raise ruminants around sugarcane industries. However, these products are not widely used by farmers due to an assumption that the usage is inefficient and that the feed utilization technology is not widely recognized. Sugarcane fibrous residues (tops, bagasse and pith) may be a potential feed component if pre-treated to increase its digestion and consumption by the animal, and/or supplemented by other ingredients to balance nutrients in the rumen as well as those for production purpose. Digestibility can be increased by chemical treatments such as ammoniation and other alkaline treatments, whereas consumption can be increased by physical treatments such as grinding, hammermilling or pelleting. Nutrients that are missing in these fibrous residues can be provided by addition of urea, molasses and minerals for maintenance need, and bypass nutrients (carbohydrates, protein and fats) that are digested in the small intestine and available for tissue or milk synthesis. There are three options for development of livestock agribusiness based on fibrous sugarcane residues; however, these require several technologies to optimize the utilization of these residues. Â Key words: Sugarcane fibrous residues, treament, supplements, ruminants